The moderating impact of regulatory policy formation, corporate governance, and economic development on the relationship between the accounting environment and control of corruption in ASEAN countries - Bhagia, Vishal (Animo Repository, 2022)
Corruption is a pressing issue that is continuously discussed by professionals in terms of understanding how to reduce it. In fact, accountants have a key role in controlling corruption through promoting transparency across the private and public sectors. Despite this, current literature has failed to consider the accounting environment together with the role of corporate governance, regulatory policy formation, and economic development in mitigating corruption within ASEAN countries. Therefore, this study proposed to address the current research gap by performing a panel regression analysis on ASEAN countries from 2010 to 2019. This study found that the accounting environment does not have a significant impact on a country’s control of corruption, implying that the current accounting environment is lacking in the scope used to define corruption as it is only focused on increasing transparency instead of targeting and catching corrupt activities. On the other hand, regulatory quality and economic development are found to have significant moderating impacts on the relationship between the accounting environment and control of corruption. As such, this study recommends strengthening the current regulatory quality, specifically in the accounting standards and practices, to further reinforce the accounting environment and consequently mitigate corruption. Finally, this study finds that the moderating impact of corporate governance is insignificant as a result of the large levels of corruption experienced in certain countries within the ASEAN.